2019
DOI: 10.3390/gidisord1010018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in the Pathogenesis of Inflammatory Bowel Disease

Abstract: Vitamin D has a complex role in the pathogenesis of inflammatory bowel disease (IBD), which is still under investigation. We conducted a literature search using PubMed through December 2018 through the use of relevant search terms. We found an abundance of evidence to support the role of vitamin D in regulating the innate and adaptive arms of the immune system. The pathogenesis of IBD implicates the immune dysregulation of these immune system components. Proof of concept of the vitamin’s role in the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In fact, vitamin D, beyond its classic role in calcium and bone homeostasis, plays a dynamic role in regulation of the immune system [17]. In the pathogenesis of immune-mediated diseases such as IBD, vitamin D is considered a paramount element [18,19]. Incidence of hypovitaminosis D is higher in patients with IBD (from 16% to 95%) than in the healthy population [20], and it is higher in patients with Crohn’s Disease than in those with Ulcerative Colitis [21].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, vitamin D, beyond its classic role in calcium and bone homeostasis, plays a dynamic role in regulation of the immune system [17]. In the pathogenesis of immune-mediated diseases such as IBD, vitamin D is considered a paramount element [18,19]. Incidence of hypovitaminosis D is higher in patients with IBD (from 16% to 95%) than in the healthy population [20], and it is higher in patients with Crohn’s Disease than in those with Ulcerative Colitis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the disease activity index score was significantly lower in the mice groups receiving low and high doses of vitamin D3 compared to the control group, and significantly lower in mice given high doses of vitamin D3 compared to the control group. 22 The IL-17 and IL-17R levels were significantly lower in mice given high doses of vitamin D3 compared to the low dose group. 23 This findings suggest that vitamin D may increase the chemotaxis and differentiation of Th1 cells by inhibiting IL-17/IL-17R signaling, thereby increasing immune function, and reducing IBD disease severity.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, single-nucleotide polymorphisms in the human VDR gene were reported to be associated with an elevated susceptibility to IBD [ 77 , 78 ]. The four most frequently studied are common VDR polymorphisms recognized by restriction enzymes: rs7975232 (c.1025-49 G > T, ApaI) and rs1544410 (c.1024 + 283 G > A, BsmI) at the 3′ flanking end of intron 8, rs731236 (c.1056 T > C, p.Ile352=, TaqI) at the 3′ flanking end of exon 9, and rs2228570 (c.2T > C, p.Met1Thr, FokI) at the 5′ end of exon 2 [ 79 , 80 ].…”
Section: Genetic Determinants Of Vitamin D Activity In Ibdsmentioning
confidence: 99%